Antibody titer after vaccination against hepatitis B virus with different schedule among patients with endstage renal disease on maintenance hemodialysis (BIRDEM Medical Journal, 2023)
Background: Infection with the hepatitis B virus (HBV) causes high morbidity. Vaccination against HBV is very important for patients receiving hemodialysis due to end-stage renal disease (ESRD). Our study aimed to find out whether 0, 1, 2 and 6 months HBV vaccination schedule produces a better antibody response than the 0, 1, 2 months or 0,1,6 months schedule with two 20 μg [1.0 mL doses] I/M injections administered in 2 sites in each dose and to find out the overall antibody status (effectiveness) of HBV vaccine in a patient with ESRD on maintenance hemodialysis.Methods: This cross-sectional study was conducted in the Department of Gastrointestinal, Hepatobiliary and Pancreatic Disorders (GHPD), Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) General Hospital, Dhaka, Bangladesh, from December 2020 to November 2021. All patients were collected from the Department of Hemodialysis and Nephrology diagnosed with ESRD and were on maintenance hemodialysis. Data were collected in a single sitting about their past vaccination status. An anti-HBs antibody test was sent to see the antibody status after vaccination against HBV.Results: In this study, a total of 100 patients were selected, aged between 40 and 82 years, and the majority of the patients (63.0%) were male. Among them, 40 (40%) patients received 0, 1, 2 months schedule and 30 (30%) patients received 0, 1, 6 and rest of 30 (30%) patients received 0, 1, 2, 6 months schedule. We found patients who used the 0,1,2,6 months schedule, 54% of them achieved protective antibodies, and for patients who used the 0,1,2 and 0,1,6 months schedule, only 27% and 19% achieved protective antibodies, respectively. Their anti- HBs (titer) mean±SD were 293.93±122.38 (IU/L) with 0,1,2,6 months schedule and 126.14±132.90 (IU/L) and 276.66±152.07 (IU/L) with 0,1,2 months and 0,1,6 months schedule respectively. Overall we found that 37 (37.0%) of the patients had protective antibodies (>100 IU/l), 29 (29.0%) with low protective antibodies (10-100 IU/L), and the remaining 34 (34.0%) respondents we7re found to have nonprotective antibody (